Investigation of Issues for the Accurate and Precise Measurement of an Analyte Using Surface-Enhanced Raman Scattering (SERS). Issue 4 (April 2019) - Skuratovsky, Aleksander; Klimenko, Anton S.; Porter, Marc D.
This paper builds on an earlier examination of the influence of sampling size and analyte surface density on the accuracy and precision of measurements using surface-enhanced Raman scattering (SERS) to read out heterogeneous immunoassays. Quantitation using SERS typically relies on interrogating a small area on the sample surface by using a micrometer-sized laser spot for signal generation. The information obtained using such a small portion of sample is then projected as being representative of the much larger sample, which can compromise the accuracy and precision of the measurement due to undersampling. For a heterogeneous immunoassay interrogated by SERS, quantitation is, therefore, sensitive to the size of the analyzed area and the surface density of the measured analyte. To identify conditions in which sampling error poses a threat to accuracy and precision, a simulation of a SERS immunoassay was developed and compared to experimental results. The simulation randomly distributes adsorbates across the capture surface and then measures the density of adsorbates inside areas of analysis of different sizes. This approach mimics the analysis of a heterogeneous immunoassay when using a Raman microscope with different laser spot sizes. The results of the simulations, which were confirmed experimentally by comparison to an immunoassay of human immunoglobulin G (IgG) show that the accuracy and precision of the measurement improved with larger analysis areas and higher analyte concentrations due to the increased apparent homogeneity of the analyte within the area of analysis. By imposing a threshold on precision (5%), we also begin to establish a framework for the parameters necessary to achieve reliable quantitative measurements (e.g., laser spot size, analyte concentration, and sample volume).